ANALISIS KONDISI PERKERASAN JALAN MENURUT METODE BINA MARGA DAN METODE PCI JALAN RAYA LINTAU – PAYAKUMBUH - Dicky Rizaldi fajri; Surya Eka Priana; Yorizal Putra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
On the Lintau - Payakumbuh highway, which connects the two areas, which are busy with light vehicles and heavy vehicles, the road surface is damaged. In this study, the authors conducted a survey on the Lintau - Payakumbuh road, Jorong Kalumpang, Nagari Lubuak Jantan, along KM 37 - KM 39, with a road width of 4.8 m. As time goes by, there is an increase in community needs in the mobility of daily activities with an increase in the volume of vehicles, resulting in damage to the pavement on this road segment. The purpose of this study was to determine the type and level of damage to the pavement that occurred on the Lintau – Payakumbuh road, Jorong Kalumpang, Nagari Lubuak Jantan with the PCI and Bina Marga methods and provide suggestions for maintenance and repair efforts. The types of damage found included crocodile cracks, subsidence, patches, longitudinal cracks, holes. In the PCI method the value obtained is 87.3 with excellent road conditions, in the Bina Marga method the priority order value is 10.6 with a routine maintenance program. From the results of the two methods, the values and results are almost the same, namely the road conditions are still in good condition. Handling road repairs by patching potholes, leveling subsidence, patching cracks on damaged roads. Routine maintenance should be carried out on this road segment in order to provide comfort for its users, such as maintenance on the shoulder of the road, drainage channels, and making rainwater barriers to avoid damage. Keywords : Analysis of road damage, PCI, Bina Marga, Demage rate, Routine maintenance.